2009
DOI: 10.1007/s10822-009-9306-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-vascular safety beyond hERG: in silico modelling of a guinea pig right atrium assay

Abstract: As chemists can easily produce large numbers of new potential drug candidates, there is growing demand for high capacity models that can help in driving the chemistry towards efficacious and safe candidates before progressing towards more complex models. Traditionally, the cardiovascular (CV) safety domain plays an important role in this process, as many preclinical CV biomarkers seem to have high prognostic value for the clinical outcome. Throughout the industry, traditional ion channel binding data are gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The activity thresholds used to distinguish blockers and nonblockers ranged from 1 to 40 μM, suggesting a high variation in the training set compositions. While some considered data extracted from single or multiple assay/data sources, most studies used in-house data or proprietary data from the pharma industry that are not publicly accessible. , A limited number of studies ,, reported classification models based on hERG data extracted from publicly accessible bioactivity databases such as ChEMBL and PubChem. The heterogeneous activity data obtained from such databases were shown to possess a considerable level of experimental uncertainty, and recommendations were made regarding how such data must be curated before model development. Additional limitations such as small numbers of compounds used in modeling (often a few hundred), narrow or unreported applicability domains, and lack of proof of validation (e.g., Y-randomization tests) restrict the use of most previously published models.…”
Section: Introductionmentioning
confidence: 99%
“…The activity thresholds used to distinguish blockers and nonblockers ranged from 1 to 40 μM, suggesting a high variation in the training set compositions. While some considered data extracted from single or multiple assay/data sources, most studies used in-house data or proprietary data from the pharma industry that are not publicly accessible. , A limited number of studies ,, reported classification models based on hERG data extracted from publicly accessible bioactivity databases such as ChEMBL and PubChem. The heterogeneous activity data obtained from such databases were shown to possess a considerable level of experimental uncertainty, and recommendations were made regarding how such data must be curated before model development. Additional limitations such as small numbers of compounds used in modeling (often a few hundred), narrow or unreported applicability domains, and lack of proof of validation (e.g., Y-randomization tests) restrict the use of most previously published models.…”
Section: Introductionmentioning
confidence: 99%